ROLE OF VITAMIN D IN PREVENTION OF ACUTE EXACERBATION OF BRONCHIAL ASTHMA IN ADULTS - Musharraf, Muhammad Usman; Sandhu, Ghaanfar Ali; Mumtaz, Muhammad Usman; Rashid, Muhammad Farhan (Journal of Postgraduate Medical Institute, 2017)
Objective: To determine role of vitamin D in prevention of acute exacerbation of bronchial asthma in adults when added to standard treatment. Methodology: The study included 80 patients of either gender with age ranging from 16 to 46 years. Bronchial asthma diagnosed for at least 1 year and vitamin D levels below 30 ng/ml, no history of smoking, intake of vitamin D 6 months before trial or other chronic diseases were included in the study. They were randomly divided into two groups by using computer generated random number table, group A and group B and were given combination of standard treatment of bronchial asthma and vitamin D vs standard treatment only respectively. Results: 25(62.5%) were male in group A while 21(52.5%) were male in group B. Mean age of study population was 29.56 ±8.06 years. Vitamin D was found more effective in prevention of exacerbations of bronchial asthma (P value 0.003). Conclusion: Vitamin D was efficacious in bronchial asthma in terms of prevention in number of exacerbations when added to standard treatment.